Study the mechanical behavior of materials under the effect of the number of notches - Bennacer Ahmida; Sadallah Adnane (University of Shahid Hama Lakhdar - El Oued, 2025)
It is necessary to study the effect of notch quantity on material behavior for the sake of preserving the structural integrity and safety. Notches are stress concentrators and have a great impact on properties like strength, toughness and fatigue life. Detailed knowledge of these influences allows for accurate failure prediction, design improvement by eliminating stress concentrations (for instance by using fillets or radii) and material selection (for example, utilization of alloys with high notch toughness or composite materials). Some of the key aspects that have been examined are stress concentration factors, sites of fracture initiation, and fatigue crack propagation. These insights are important in many areas such as aerospace (fuselage connections, wing assemblies), automotive engineering (chassis, engine components), civil construction (steel connections, reinforced concrete) and manufacturing (machined and welded structures). Eventually, such information helps to create safer, lighter, and more durable products in a wide range of engineering domains. من الضروري دراسة تأثير عدد الثقوب على سلوك المواد بهدف الحفاظ على السلامة الهيكلية والأمان. تعتبر الثقوب مُركِّزات للإجهاد ولها تأثير كبير على خصائص مثل القوة والمتانة وعمر الإجهاد. تسمح المعرفة التفصيلية لهذه التأثيرات بالتنبؤ الدقيق بالفشل، وتحسين التصميم عن طريق إزالة مُركِّزات الإجهاد (على سبيل المثال باستخدام التقوسات أو الأنصاف) واختيار المواد (على سبيل المثال، استخدام سبائك ذات مقاومة عالية للكسر في وجود الشقوق أو المواد المركبة). بعض الجوانب الرئيسية التي تم فحصها هي معاملات تركيز الإجهاد، ومواقع بدء الكسر، وانتشار شقوق الإجهاد. هذه الرؤى مهمة في العديد من المجالات مثل الفضاء الجوي (وصلات جسم الطائرة، وتجميعات الأجنحة)، وهندسة السيارات (الشاسيه، ومكونات المحرك)، والإنشاءات المدنية (وصلات الصلب، والخرسانة المسلحة) والتصنيع (الهياكل المشغولة والمُلحمة). في النهاية، تساعد هذه المعلومات في إنشاء منتجات أكثر أمانًا وأخف وزنًا وأكثر متانة في مجموعة واسعة من المجالات الهندسية.
Master's thesis specializing in energy
Keywords: the structural integrity and safety- engineering domains; السلامة الهيكلية والأمان – المجالات الهندسية.